Streamlining Charity Management: SIMBA's Impact on Zakat, Infaq, and Sadaqah at Baznas Bukittinggi - Riani, Deni (Al Urwah : Sharia Economics Journal, 2024)
This study explores how BAZNAS Bukittinggi City manages zakat, infaq, and sadaqah through the SIMBA application. It employs a qualitative approach with interviews, observation, and documentation for data collection. Data analysis involves reducing, presenting, and drawing conclusions, validated through triangulation. Results indicate BAZNAS Bukittinggi City's focus on effectiveness in charity management. Factors aiding SIMBA include supportive leadership policies, skilled operators, and robust IT infrastructure. Challenges include SIMBA's reliance on internet connectivity and a shortage of qualified IT personnel. This research sheds light on the effectiveness and challenges of utilizing SIMBA for charity management in BAZNAS Bukittinggi City.